Cow´s milk and its implications in the transmission of infectious diseases (Ágora de Heterodoxias, 2017)
Food industry is responsible for the largest trade in the world. Human and animal health regulators agencies are in charge for ensuring an important part of public health, motivated that food from animal origin, constitute a potential risk of infections and toxic-infections, and they are an excellent vehicle for microorganisms causing diseases in humans and animals. Food-borne diseases are a daily cause of a significant percentage of morbidity and mortality worldwide. At least 200 microorganisms such as enterobacteria and some bacteria with zoonotic potential, generate greater challenges to food industry. The epidemiology of these diseases is changing, with new pathogens spreading rapidly around the world. Many of these microorganisms have reservoirs in apparently healthy animals, making difficult to detect them and making the problem more far-reaching. Cow's milk is one of the most important vehicle of transmission for this type of disease in the world with many microorganisms involved, some causing diseases in animals but others being normal digestive or mammary flora in animals. Many studies have been done to describe pathogens associated with food-borne diseases and zoonoses, most of them standardized under the critical control point system. Therefore, it is important to make an approach to these studies and the methodologies described for control of food-borne diseases, with an emphasis on milk production.
Keywords: food-borne diseases; cow’s milk; bacteriology and public health